ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BELI KONSUMEN PRODUK MAKANAN DAN MINUMAN "HALAL"DI KOTA BATAM - Putra, Edy Yulianto; Fang, Yockie (Journal of Global Business and Management Review, 2020)
This research is to detect the factors that impact the purchase intention of "Halal" food and drink product consumer in Batam City. The Independent variables are Subjective Norm, Religiousity, Product Quality, Attitude as intervening variable and the dependent variable is Purchase intention. This research exploit consumer that look forward to buy "Halal" food and drink product ABC, Nestle, NESCAFE, and other brands. The adopted data was 330. Purposive Sampling was used as sampling method in this research, conclude there was a positive significant effect between the Subjective Norm, Religiousity, Product Quality and Attitude on Purchase Intention.